2007
DOI: 10.1111/j.1365-2702.2006.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evidence for suboptimal compliance of healthcare practitioners to standard/universal infection control precautions

Abstract: Compliance to infection control precautions is internationally suboptimal. The evidence confirms that compliance to specific aspects of standard/UPs varies, and practitioners are selective in their application of recommended practice. Compliance does improve following a structured intervention; however, research fails to indicate for how long the intervention affects practitioner compliance, or whether compliance after a period of time returns to the norm. Several reasons for non-compliance are discussed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
3
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 61 publications
(122 reference statements)
8
136
3
22
Order By: Relevance
“…Studies typically did not clearly report the population characteristics of the two groups or control any potential differences, thus making comparisons difficult and potentially subject to bias. Few studies monitored compliance with infection control measures, which has been reported to frequently be suboptimal 71. High levels of compliance may be necessary for certain infection control measures to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Studies typically did not clearly report the population characteristics of the two groups or control any potential differences, thus making comparisons difficult and potentially subject to bias. Few studies monitored compliance with infection control measures, which has been reported to frequently be suboptimal 71. High levels of compliance may be necessary for certain infection control measures to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Munoz-Price et al 45 noted that their experience suggested failure to comply with "isolation precautions" was common. An international review of the compliance of healthcare staff with infection control interventions found this to be sub-optimal but also highlighted that structured interventions can improve compliance 60 .…”
Section: Key Findingsmentioning
confidence: 99%
“…[5][6][7] Compliance rates from as low as 30% for facemask use and 38% for use of eye protection have been reported. 8 Hand washing, the most basic of infection control measures, has been reported to be adhered to only approximately 40% of the time. 6 compliance; and 'not re-sheathing needles'-high favourable attitude (86%) but low compliance.…”
Section: Introductionmentioning
confidence: 99%